Etchability Dependence of InOx and ITO Thin Films by Plasma Enhanced Reactive Thermal Evaporation on Structural Properties and Deposition Conditions. (30th January 2018) - Amaral, Ana; Lavareda, G.; Nunes de Carvalho, C.; André, V.; Vygranenko, Yuri; Fernandes, M.; Brogueira, Pedro
ABSTRACT: Indium oxide (InOx ) and indium tin oxide (ITO) thin films were deposited on glass substrates by plasma enhanced reactive thermal evaporation (PERTE) at different substrate temperatures. The films were then submitted to two etching solutions with different chemical reactivity: i) HNO3 (6%), at room temperature; ii) HCl (35%): (40 °Bé) FeCl3 (1:1), at 40 °C. The dependence of the etchability of the films on the structural and deposition conditions is discussed. Previously to etching, structural characterization was made. X-ray diffraction showed the appearance of a peak around 2θ=31° as the deposition temperature increases from room temperature to 190 °C, both for ITO and InOx . AFM surface topography and SEM micrographs of the deposited films are consistent with the structural properties suggested by X-ray spectra: as the deposition temperature increases, the surface changes from a finely grained structure to a material with a larger-sized grain or/and agglomerate structure of the order of 250-300 nm. The roughness Rq varies from 0.74 nm for the amorphous tissue to a maximum of 10.83 nm for the sample with the biggest crystalline grains. Raman spectra are also presented.